2015
DOI: 10.3402/iee.v5.28877
|View full text |Cite
|
Sign up to set email alerts
|

How can health systems be strengthened to control and prevent an Ebola outbreak? A narrative review

Abstract: The emergence and re-emergence of infectious diseases are now more than ever considered threats to public health systems. There have been over 20 outbreaks of Ebola in the past 40 years. Only recently, the World Health Organization has declared a public health emergency of international concern (PHEIC) in West Africa, with a projected estimate of 1.2 million deaths expected in the next 6 months. Ebola virus is a highly virulent pathogen, often fatal in humans and non-human primates. Ebola is now a great priori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 39 publications
2
35
0
Order By: Relevance
“…This led to a series of surveillance training workshops and creation of an Ebola incident management system which is thought to have enhanced preparedness and reduced Ebola case burden in the region compared to other areas of the country. (Jacobsen et al, 2016;Kaufman, 2008;Zumla et al, 2016) − Indicator based surveillance (Balajee et al, 2016;Kruk et al, 2015;Lapao et al, 2015;Nyenswah et al, 2016;Regmi et al, 2015) − Event based surveillance (Adokiya & Awoonor-Williams, 2016;Balajee et al, 2016;Espinal et al, 2016;Forrester et al, 2014;Garcia Serpa Osorio-de-Castro, Silva Miranda, Machado de Freitas, Rochel de Camargo, & Cranmer, 2017;Kruk et al, 2015;Lapao et al, 2015;McPake et al, 2015;Nyarko et al, 2015;Nyenswah et al, 2016;Regmi et al, 2015;Stoto et al, 2013;Thiam et al, 2015), with use of community health monitors (Balajee et al, 2016;Jacobsen et al, 2016;Martineau, 2016;McPake et al, 2015;Nyarko et al, 2015;Nyenswah et al, 2016;Regmi et al, 2015;Scott et al, 2016;Thiam et al, 2015) − Verification of reported signal events (Balajee et al, 2016;Espinal et al, 2016;Lapao et al, 2015;Nyenswah et al, 2016;Regmi et al, 2015;Siedner et al, 2015) − Appropriate referral of suspected cases (Siekmans et al, 2017;Thiam et al, 2015...…”
Section: Surveillancementioning
confidence: 99%
See 4 more Smart Citations
“…This led to a series of surveillance training workshops and creation of an Ebola incident management system which is thought to have enhanced preparedness and reduced Ebola case burden in the region compared to other areas of the country. (Jacobsen et al, 2016;Kaufman, 2008;Zumla et al, 2016) − Indicator based surveillance (Balajee et al, 2016;Kruk et al, 2015;Lapao et al, 2015;Nyenswah et al, 2016;Regmi et al, 2015) − Event based surveillance (Adokiya & Awoonor-Williams, 2016;Balajee et al, 2016;Espinal et al, 2016;Forrester et al, 2014;Garcia Serpa Osorio-de-Castro, Silva Miranda, Machado de Freitas, Rochel de Camargo, & Cranmer, 2017;Kruk et al, 2015;Lapao et al, 2015;McPake et al, 2015;Nyarko et al, 2015;Nyenswah et al, 2016;Regmi et al, 2015;Stoto et al, 2013;Thiam et al, 2015), with use of community health monitors (Balajee et al, 2016;Jacobsen et al, 2016;Martineau, 2016;McPake et al, 2015;Nyarko et al, 2015;Nyenswah et al, 2016;Regmi et al, 2015;Scott et al, 2016;Thiam et al, 2015) − Verification of reported signal events (Balajee et al, 2016;Espinal et al, 2016;Lapao et al, 2015;Nyenswah et al, 2016;Regmi et al, 2015;Siedner et al, 2015) − Appropriate referral of suspected cases (Siekmans et al, 2017;Thiam et al, 2015...…”
Section: Surveillancementioning
confidence: 99%
“…Epidemiologists to define/validate signal events and translate data into public health interventions (Balajee et al, 2016;Siedner et al, 2015) . Adequate staff numbers: doctors, nurses, CHWs (Adokiya & Awoonor-Williams, 2016;Boozary et al, 2014;Cancedda et al, 2016;Espinal et al, 2016;Forrester et al, 2014;Gostin & Friedman, 2015;Kieny et al, 2014;Kruk et al, 2015;Lapao et al, 2015;McPake et al, 2015;Mulinge & Soyemi, 2016;Regmi et al, 2015;Siedner et al, 2015;Siekmans et al, 2017); also at sub-regional level (Gostin & Friedman, 2015;Kruk et al, 2015;Regmi et al, 2015) . Health worker training and continuing education (Adokiya & Awoonor-Williams, 2016;Boozary et al, 2014;Cancedda et al, 2016;Espinal et al, 2016;Forrester et al, 2014;Gostin & Friedman, 2015;Kruk et al, 2015;Lapao et al, 2015;McPake et al, 2015;Mulinge & Soyemi, 2016;Nyarko et al, 2015;Regmi et al, 2015;Siedner et al, 2015;Siekmans et al, 2017;Thiam et al, 2015); understanding of community knowledge and beliefs (Buseh et al, 2015;Dhillon & Kelly, 2015;Martineau, 2016;Regmi et al, 2015;Scott et al, 2016;…”
Section: Surveillancementioning
confidence: 99%
See 3 more Smart Citations